USING METACOGNITIVE METHOD TO IMPROVE PERFORMANCE IN MATHEMATICAL AMONG PRIMARY SCHOOL STUDENTS IN EBONYI STATE, NIGERIA (IJOVTECH, 2026)
Concern is rising over the prevalence of a negative view of mathematics in Nigeria's classrooms. Several studies have highlighted effective strategies for overcoming the problem of negative math attitudes. However, there is a lack of information about how metacognitive instruction can help students develop positive attitudes toward mathematics. This study used a quasi-experimental design to investigate how the metacognitive instruction strategy influenced the mathematical dispositions of secondary school students in Ebonyi State.  Ninety-one (n = 91) students comprising males and females between the ages of 10 and 14 years with a mean age of (M=9.14) and (SD= 1.24) were randomly selected from different public secondary schools in Ebonyi State as the study participants. The participants were grouped into two and were subjected to a pre-test and post-test study. The independent t-test conducted on the data following the pre-test and post-test studies proved that Metacognition enhanced the participants' mathematical attitudes at MD = 13.65 (95% CI, 8.91 to 16.17), t (89) = 6.328, p = .001. Thus, the result supported the study's hypothesis. It was concluded that Metacognition is effective in enhancing students' mathematics attitudes. The study recommends regularly training teachers on using the metacognitive approach in the classroom.